Crosstalk Between Trophoblasts and Decidual Immune Cells: The Cornerstone of Maternal-Fetal Immunotolerance - Xu, Ling; Li, Yanhong; Sang, Yifei; Li, Da-Jin; Du, Meirong (Frontiers in Immunology, 2021)
The success of pregnancy relies on the fine adjustment of the maternal immune system to tolerant the allogeneic fetus. Trophoblasts (Tros) carrying paternal antigens are the only fetal-derived cells that come into direct contact with the maternal immune cells at the maternal-fetal interface. The crosstalk between Tros and decidual immune cells (DICs) via cell-cell direct interaction and soluble factors such as chemokines and cytokines, is the core event contributing to the unique immunotolerant microenvironment. Abnormal Tros-DICs crosstalk can lead to dysregulated immune situation, which is well-known to be a potential cause of a series of pregnancy complications including recurrent spontaneous abortion (RSA), the most common one. Immunotherapy has been applied to RSA. However, its development was far less rapid or mature than cancer immunotherapy. Elucidating the mechanism of maternal-fetal immune tolerance, the theoretical basis for RSA immunotherapy, not only helps to understand the establishment and maintenance of normal pregnancy, but also provides new therapeutic strategies and promotes the progress of immunotherapy against pregnancy-related diseases caused by disrupted immunotolerance. In this review, we focus on recent progress in the maternal-fetal immune tolerance mediated by Tros-DICs crosstalk and clinical application of immunotherapy in RSA. Advancement in this area will further accelerate the basic research and clinical transformation of reproductive immunity and tumor immunity.